Relationship between SYNTAX score and myocardial viability in ischemic cardiomyopathy - Semi Öztürk; Ahmet Seyfeddin Gürbüz; Cevat Kırma (KARE Publishing, 2019)
Objective: The SYNTAX score (SS) is not just a measure of the severity of coronary artery disease, but also complexity. The aim of this study was to evaluate the relationship between the SS and myocardial viability/non-viability assessed by positron emission tomography (PET) in patients with ischemic cardiomyopathy (IC). Methods: A total of 107 IC patients who had undergone PET were enrolled in the study. The patients were divided into two groups according to the presence or absence of viable myocardium. SS was analyzed from recorded conventional coronary angiographies. Results: Patients with a non-viable myocardium (n=21; 19.6%) had a significantly higher SS compared to those with a viable myocardium (17.6+-3.7 vs. 14.1+-5.2, respectively; p=0.004). Point-biserial correlation coefficient analysis indicated that the presence of myocardial non-viability was mildly correlated with a higher SS (rpb=-0.28, p=0.004). In multivariate logistic regression analysis, the SS was identified as the sole independent predictor of myocardial non-viability (odds ratio [OR]: 1.164, 95% confidence interval [CI]: 1.044-1.297; p =0.006]. Receiver operating characteristic analysis revealed a cutoff point of 16 for predicting a non-viable myocardium (area under curve: 0.71, 95% CI: 0.61-0.82) with a sensitivity of 76.2% and a specificity of 61.6%. Conclusion: The results of the present study indicates that a high SS is associated with the presence of a non-viable myocardium in IC patients.